Estudios en Festuca elevada (II). Efecto de la defoliación y nitrógeno en primavera sobre los tallos vegetativos - Manzano Ramos-Izquierdo, Juan A. (Pastos, 2011)
R E S U M E N Una pradera de festuca elevada, cv. S.170, fue sometida a cuatro tratamientos (dos intervalos de corte por dos niveles de nitrógeno) durante la primavera. El efecto de estos tratamientos sobre los tallos vegetativos medido en aspectos morfológicos, proteína bruta e hidratos de carbono solubles es estudiado. S U M M A R Y The effects of two cutting managements and two levels of nitrogen on tillering pattern were compared in an established Tall Fescue S. 170. The cutting treatments were cutting every three weeks and cutting at a relatively mature (silage) stage. The nitrogen rates were 75 and 150 Kg. N/Ha. up to June. The tillers were divided in two categories by weight. All categories occurred in the frequently cut treatments but in the silage treatments the highest category was not present. The dry matter percentage of each blade and sheath of the vegetative tiller population was similar in all treatments. Data on chemical composition of the different leaves are presented. Factors affecting the structure of tiller population are discussed.